ANALISIS POSTUR KERJA DAN USULAN PERBAIKAN DENGAN PERANCANGAN ALAT PADA PEKERJA DI PABRIK KERUPUK ERNA MELALUI PENDEKATAN ERGONOMI - Afifah Wahyu Ramadanti (2022)
There are still many small industrial production processes in Indonesia that use the traditional manual method carried out by human labor in the production process, to be precise at one of the cracker factories in Bekasi. Problems were found in workers in the section of transferring steamed crackers from the steamer rack to traditional containers and then moving to a drying area for ±10 meters, these workers did the work repeatedly and back and forth with non-ergonomic postures, causing a high possibility of musculoskeletal disorders risk. In this study, an analysis of work posture is carried out using a virtual environment model through the Nordic Body Map, Rapid Entire Body Assessment, and Posture Evaluation Index methods and will provide suggestions for improvement by designing a folding trolley rack to reduce this risk. After analyzing the work posture, the initial REBA and PEI results were 14 and 3.34, which means the risk of injury in these work activities is very high. Then made the designed a folding trolley rack with dimensions of 196 x 93 x 103 cm with four collapsible adjuster shelves. The results of the REBA and PEI analysis after using the tool design are 5 and 1.22, which means that there is a decrease in risk from the very high category to the medium level.